(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
For the neutralization of the products of incomplete combustion of gas emissions from industry, the most accessible and profitable is dry chemical transformation with subsequent binding, which allows the transformation of incomplete combustion at high temperatures and with a low content of it in the gas mixture and ultimately obtain non-aqueous compounds. The catalytic-chemisorption method of gas purification is based on chemical afterburning on the surface of the catalytic system.